If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 2h + -5 Reorder the terms: 3 = -5 + 2h Solving 3 = -5 + 2h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2h' to each side of the equation. 3 + -2h = -5 + 2h + -2h Combine like terms: 2h + -2h = 0 3 + -2h = -5 + 0 3 + -2h = -5 Add '-3' to each side of the equation. 3 + -3 + -2h = -5 + -3 Combine like terms: 3 + -3 = 0 0 + -2h = -5 + -3 -2h = -5 + -3 Combine like terms: -5 + -3 = -8 -2h = -8 Divide each side by '-2'. h = 4 Simplifying h = 4
| =120-(4*150) | | 2y-4x=-20 | | 2=20-2w | | -9-(-21)+(-24)-19= | | 3=9-3j | | X-8+2=0 | | 21b=2(4) | | 105+8x-4=14(5+2x)-9 | | 3b-14=4 | | 25X(x-5)= | | 38=47-v | | n=.6n+5.3 | | 54=43+x | | 9=-2+w | | 120-(4*150)= | | 5y-30=20 | | 7+2c=15 | | M+15=-15p | | 7+2c=1 | | V-6=-2 | | 5x+15-9=32 | | 120-(4*120)= | | 3x+12=36-5y | | 3x+19=10x+18 | | 2d-5=1 | | -5a=29 | | 13=7+2z | | 1+2t^3-3t^2=0 | | -4y+3=3x | | 4(x-9)-3=-5x+9(x+8) | | 3x^5-x^4-14x^3=0 | | 2x+3x+15-9=32 |